Islamic Academic Supervision Model: Enhancing the quality of Islamic religious education in Muhammadiyah junior high schools - Akhmad Fakhrur Rouzi; H. Husamah; B. Budiono; Hawaree Lambensa (Universitas Muhammadiyah Malang, 2025)
The need to improve the quality of Islamic Religious Education (PAI) in faith-based schools has become increasingly urgent as teachers face challenges of professional competence, administrative burden, and limited supervisory support that hinder effective classroom practice. This study investigates the Islamic Academic Supervision Model (IASM) as an empirically grounded framework for enhancing the quality of PAI learning in Muhammadiyah junior high schools in Malang, Indonesia. Using a qualitative case study design, the research explored supervisory practices, challenges, and their implications for instructional quality improvement. The study was conducted at four Muhammadiyah junior high schools or Sekolah Menengah Pertama (SMP)—SMP Muhammadiyah 1, 2, 4, and 6—between January and June 2025. Data were gathered through in-depth interviews, classroom observations, and document analysis involving principals, Islamic teachers, students, and a supervisor from the Ministry of Religious Affairs. Triangulation of sources and methods and member checking ensured credibility, while data were analyzed using the Miles and Huberman interactive model. Findings show that supervision follows structured, collaborative, and reflective stages: (1) planning and scheduling, (2) classroom observation, (3) evaluation and feedback, and (4) follow-up. Constraints include time limitations, overlapping duties of principals, and inadequate facilities, but effective supervision improved teachers’ pedagogical competence, documentation, classroom management, and student engagement. The IASM emphasizes spiritual-reflective dialogue, contextual evaluation, and collaborative improvement, integrating Islamic values with professional standards. This model strengthens the pedagogical and moral dimensions of teaching, enhances learning quality and students’ religious character, and serves as a replicable framework for faith-based schools pursuing holistic quality assurance.